Studi Penggunaan Antidislipidemia Pada Pasien Stroke Iskemik (Penelitian dilakukan di RSUD R.T. Notopuro Sidoarjo) - Ilfi Hanna, Az Zahra; Hasmono, Didik; Issaura, Issaura; Syifa, Nailis (Indonesian Journal of Pharmaceutical Education, 2024)
Stroke is a neurologic deficit resulting from damage to the brain due to disruption of blood flow that occurs suddenly and rapidly. 87% of strokes are ischemic strokes, caused by a lack of oxygen supply to the brain due to embolism, thrombus or atherosclerosis. Blockage of blood flow will disrupt cell function accompanied by necrosis which can then lead to infarction. Antidyslipidemia is given to all ischemic stroke patients as secondary therapy and prevention of recurrent stroke. The use of Antidyslipidemia in ischemic stroke patients improves lipid abnormalities, reduces the occurrence of coronary heart disease, and improves clinical outcomes. This study aim to describe the use pattern of antidyslipidemia in ischemic stroke patients at RSUD R.T. Notopuro Sidoarjo. The type of this research is observational research with retrospective data collection method for the period October 2023 - December 2023 and then analyzed descriptively. The pattern of antidyslipidemia use is a single use pattern, as many as 78 patterns (99%). The most common single use pattern was given atorvastatin (1 x 20 mg) as many as 66 patients (86%). The combination usage pattern given was atorvastatin (1 x 20 mg) po + fenofibrate (1 x 300 mg). The switching use pattern of atorvastatin (1 x 40 mg)po atorvastatin (1 x 20 mg)po was given to 1 patient.